Light as a potential treatment for pandemic coronavirus infections: A perspective - Enwemeka, Chukuka Samuel (J Photochem Photobiol B, 2020)
The recent outbreak of COVID-19, which continues to ravage communities with high death tolls and untold psychosocial and catastrophic economic consequences, is a vivid reminder of nature's capacity to defy contemporary healthcare. The pandemic calls for rapid mobilization of every potential clinical tool, including phototherapy—one of the most effective treatments used to reduce the impact of the 1918 “Spanish influenza” pandemic. This paper cites several studies showing that phototherapy has immense potential to reduce the impact of coronavirus diseases, and offers suggested ways that the healthcare industry can integrate modern light technologies in the fight against COVID-19 and other infections. The evidence shows that violet/blue (400–470 nm) light is antimicrobial against numerous bacteria, and that it accounts for Niels Ryberg Finsen's Nobel-winning treatment of tuberculosis. Further evidence shows that blue light inactivates several viruses, including the common flu coronavirus, and that in experimental animals, red and near infrared light reduce respiratory disorders, similar to those complications associated with coronavirus infection. Moreover, in patients, red light has been shown to alleviate chronic obstructive lung disease and bronchial asthma. These findings call for urgent efforts to further explore the clinical value of light, and not wait for another pandemic to serve as a reminder. The ubiquity of inexpensive light emitting lasers and light emitting diodes (LEDs), makes it relatively easy to develop safe low-cost light-based devices with the potential to reduce infections, sanitize equipment, hospital facilities, emergency care vehicles, homes, and the general environment as pilot studies have shown.